Study of Н2О line broadening and shifting by N2 pressure in the 16, 600–17, 060 cm−1 region using FT-spectrometer with LED source. (November 2018) - Serdyukov, V.I.; Sinitsa, L.N.; Vasilchenko, S.S.; Lavrentieva, N.N.; Dudaryonok, A.S.; Scherbakov, A.P.
Highlights: N2 -broadening and shifting coefficients for 288 H2 O transitions of the ν1   + 4ν2   + 2ν3, 3ν1   + 2ν2   + ν3, 4ν1   + ν3, 4ν1   + 2ν2, 5ν1 bands. Comparison of experimental H2 16 O-N2 line parameters versus simulation based on the HITRAN2016 list. Abstract: N2 pressure broadening and shifting coefficients are presented for about 300 strongest water vapor lines in the 16, 600–17, 060 cm −1 spectral region. The spectra have been recorded with a spectral resolution of 0.05 cm −1 at room temperature by a Fourier transform spectrometer using a high luminance LED light source. A high signal-to-noise ratio (S/N ≈ 10 000) permits the analyses of the lines with intensities from 1.54 × 10 −23 to 2.0 × 10 −26  cm/molecule. The multi-spectrum fitting procedure was used to fit line parameters of the ν1   + 4ν2   + 2ν3, 3ν1   + 2ν2   + ν3, 4ν1   + ν3, 4ν1   + 2ν2, 5ν1 bands for the temperature T  = 297 K. Line broadening and shifting calculations are performed using a semi-empirical method, which is based on the impact theory of broadening, and includes the correction factors whose parameters were determined by fitting the broadening coefficients of 12 lines to the experimental data. The method was further developed for the estimate of line profiles using the an harmonic wave functions.